Program Pojok Baca Untuk Meningkatkan Kemampuan Literasi dan Numerasi Siswa Sekolah Dasar di Desa - Darmadi; Cicilia Novi Primiani; Sudarmiani; Pujiati; Sanusi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Student learning in rural elementary schools during the Covid-19 pandemic has an impact on learning motivation. Learning activities in Purworejo Village, Pilangkenceng, Madiun Regency during the Covid-19 Pandemic experienced obstacles. Learning using information technology cannot run optimally. Many elementary school students lack motivation in reading and arithmetic. The purpose of service activities is to improve student literacy and numeracy through the reading corner program. The target of this service activity is elementary school students in Purworejo Village, Kacan Pilangkenceng, Madiun Regency. The service method is carried out with assistance, including survey activity procedures, socialization, training, learning, and evaluation. The results of the implementation of the "Reading Corner" program activities can increase students' independence by 60%, and increase literacy-numeracy skills by 50%. The activity of the "Reading Corner" program can be followed up as a digital corner program as an effort to develop digital literacy in the village.